Dietary evaluation of cinnamaldehyde supplementation with different protein energy levels and ratios in Pacific whitleg Shrimp Litopenaeus vannamei - Andri Hendriana; Mia Setiawati; Dedi Jusadi; Muhammad Agus Suprayudi; Julie Ekasari; Dinamella Wahjuningrum (Jurnal Akuakultur Indonesia)
This study aimed to evaluate the growth performance and carbohydrate metabolism of Pacific whiteleg shrimp after feeding with different cinnamaldehyde concentrations and protein-energy ratios. The study used a completely randomized design with six treatments in triplicates. The treatments were S003213; treatment S053213; treatment S052814; treatment S102814; treatment S052815; and treatment S102815. The study was conducted for 56 days in a 76 L volume aquarium using shrimps with 1.38 ± 0.01 g at 200 individuals/m3. The results showed that the S053213 treatment was significantly different (P<0.05) compared to other treatments for the specific growth rate (SGR). Hexokinase (hk) and phosphoenolpyruvate carboxykinase (pepck) produced by the S053213 treatment were significantly different (P<0.05) from the S003213 treatment. The S052815 and S102815 treatments produced higher protein retention (PR) and protein efficiency ratio (PER) compared to other treatments (P<0.05) and also produced the same final average weight (FW) as the S003213 treatment. This research shows that vannamei fed by 0.10% supplementation dose of cinnamaldehyde with a decreased feed protein up to 28% and C/P ratio 14 and 15 are able to utilize feed as well as protein 32% without cinnamaldehyde. The addition of cinnamaldehyde with a higher C/P ratio requires a higher dose of cinnamaldehyde than the optimal dose.